'Athletes', 'talents', and 'players': conceptual distinctions and considerations for researchers and practitioners - Grainger, A.; Kelly, A. L.; Garland, S. W.; Baker, J.; Johnston, K.; McAuley, A. B. T. (Sports Medicine, 2025)
A clearer understanding of, and tighter boundaries between, terms are important for researchers designing studies as well as for other sport stakeholders creating evidence-informed policies. This article considers the terms `athlete`, `talent`, and `player` from psychological and sociocultural perspectives and in different sporting communities to highlight the importance of terminological clarity in sport research. We present considerations to clarify the use of these terms within different contexts and how the use of specific terms may affect knowledge mobilization in diverse sporting populations. A conceptual discussion is provided to help operationalize development-related terminology and its associated stages, to better reflect contemporary academic thought, and enhance practical interpretations. Importantly, we also call for greater transparency from researchers when presenting findings and encourage practitioners to clearly define key terms when working in sport. Our intention in this paper is to energize readers to consider how we use language in athlete identification and development contexts, to stimulate deeper thought and discourse around the possible implications these terms may have at any point of an individual`s development in sport. Greater deliberation, identification, and acknowledgment of the drawbacks accompanying these terms will be needed before more confident assertions can be made on how researchers and practitioners could (or even should) implement certain terminology across youth sport contexts moving forward. This paper adds to a growing literature on the importance of clarity in terminology and acts as an impetus for those working in specific sports to co-design key terms used by researchers, practitioners, and policy makers.